Pengaruh Variasi Dosis Latihan Isotonik Terhadap Peningkatan Kekuatan Otot Quadriceps Femoris Pada Usia Lanjut - Maisarah, Maisarah, Totok Budi Santoso, SST.FT, MPH, Agus Widodo SST.FT, M.Fis (2015)
Background: The decrease of visible physiological function in the elderly is a muscle mass decrease. This is an important factor which resulted in the decrease of muscle strength. Previous researchers have revealed that muscular performance decreases more rapidly in the lower limbs than upper limbs; one group of lower limbs muscles which are important for mobility is the quadriceps femoris muscle group. The decreased of muscle strength is related to functional ability, especially the ability of mobility such as walking speed decrease, balance decrease and higher risk to fall. According to research done by Pujiatun (2001) stated that the increase in quadriceps femoris muscle strength is significantly better in the isotonic exercise group compared to isometric exercise group. Objective: To determine the effect of different isotonic exercise at 3 times a week with 4 times a week to increase the strength of quadriceps femoris muscle in the elderly. Methods: The study was considered Quasi Experimental, with Pre and Post Test research design Without Control Group Design. The sampling technique used was purposive sampling. The number of samples was 10 people which were divided into 2 groups. The study was conducted for 4 weeks. Leg muscle strength measurements were done by using a dynamometer. The analysis of data was done by using Wilcoxon test, the comparison effect of isotonic exercises was done by using chi square test, whereas the different effect of the two test groups was done by using Mann-Whitney test. Results: Based on the statistical test, it was obtained p value .008 where p <0.05 which means that Ha is accepted. This means that there is a significant effect of isotonic exercises to increase the muscle strength and there is no difference between the two exercises to increase quadriceps femoris muscle strength in the elderly. Conclusion: isotonic exercises 4 times a week can give better effect to increase quadriceps femoris muscle strength in the elderly. Keywords: exercises dosage, isotonic exercises, quadriceps femoris muscle strength.